(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
While the recycled concrete aggregate (RCA) reduces the need for natural aggregate, the use of recycled concrete aggregate (RCA) in place of natural aggregate (NA) in concrete is becoming more and more popular in the building sector. Furthermore, The utilization of Recycled Concrete Aggregate (RCA) provides a viable approach to addressing the environmental issue stemming from concrete waste in Mosul city. This paper investigates the effect of acidic curing environment concerning the compressive strength, mass loss, and ultrasonic pulse velocity (UPV) at different ages cured in water containing a 5% concentration Sulphuric acid (H2SO4). The density, UPV, and compressive strength were negatively impacted by an acidic curing environment for all Recycled Aggregate Concrete (RAC) mixtures. On the other hand, the concrete contains calcium-based chemical compounds, namely hydroxide of calcium (Ca(OH)2) and hydrates of calcium silicate (C-S-H), dissolves when sulfuric acid incorporates with them. This reduces the amount of binding materials within the concrete matrix, which, in turn, weakens the structure, and sulfuric acid in contact with calcium-containing materials in the concrete can form gypsum (calcium sulfate dehydrate, (CaSO4.2H2O). Gypsum formation can occupy a larger volume than the original calcium compounds, leading to expansion, cracking, and hence a growth in mass loss and a decrease in UPV and compressive strength.